5-Flourouracil-Induced Encephalopathy in Parkinson's Disease - DANE, FAYSAL; YUMUK, PERRAN FULDEN (AKAD DOKTORLAR YAYINEVI, 2012)
A 59 year-old male with Parkinson's disease developed encephalopathy during adjuvant treatment of rectal cancer. Acute neurotoxicity related to high dose 5-Flourouracil infusion is well described, but encephalopathy with low dose bolus 5-Flourouracil is rare. The advanced Parkinson's disease patients may be more prone to hyperammonemia associated encephalopathy caused by 5-Flourouracil. The prompt recognition of the symptoms is key to diagnosis and treatment.
Keywords: Parkinson's disease; 5-Flourouracil; Rectum cancer; Encephalopathy; NEUROTOXICITY; 5-FLUOROURACIL; FLUOROURACIL; INFUSION